2011
DOI: 10.3340/jkns.2011.50.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Seizure Attack in a Patient with Spinal Metastasis Diagnosed as Posterior Reversible Encephalopathy Syndrome

Abstract: A 52-year-old woman with advanced gastric cancer, which was diagnosed 7 months prior to admission, presented with low back pain and radiculopathy in the left leg. The primary tumor was not resectable, and 10 cycles of chemotherapy with FOLFOX (5-Fluoruracil/Oxaliplatin) had been completed 23 days prior to admission. A metastatic tumor with an epidural extension was detected at the 4th lumbar vertebra (Fig. 1A). As a result, elective surgical decompression and stabilization were scheduled. Two days before the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…17 We have found 4 other cases of PRES associated with oxaliplatin [18][19][20][21] and 1 other case similar to ours after treatment with both oxaliplatin and 5-fluorouracil. 22…”
Section: Discussionmentioning
confidence: 99%
“…17 We have found 4 other cases of PRES associated with oxaliplatin [18][19][20][21] and 1 other case similar to ours after treatment with both oxaliplatin and 5-fluorouracil. 22…”
Section: Discussionmentioning
confidence: 99%
“…They are posterior reversible encephalopathy, Wernicke's encephalopathy, and hyperammonemic encephalopathy. [ 2 3 ] It is the diagnosis of exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In a review performed in Pubmed, we found two cases that showed the use of FOLFOX preceding this syndrome [8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…As a result of typical imaging features, PRES was diagnosed. An antiepileptic drug was administered and no more seizures were reported [9]. …”
Section: Discussionmentioning
confidence: 99%